Decision-Making Mechanism For Effective Management оf Equity Capital іn аn Enterprise - PARII, L. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article describes development of managerial decisions regarding capital management at the enterprise. Nowadays, the struggle intensifies among enterprises for market getting and high profit. The solution of this situation is the rationale behind the decision on long-term and short-term management of enterprises. That`s why assessment of the impact management decisions on the management of own capital at the enterprise and determining the main priority areas is an extremely important issue in modern conditions. The achievement of the goal is possible only by increasing competitiveness. If a company has competitive advantages, it will be able to actively interact with the external environment and be able to constantly develop. This is facilitated by effective action of management staff to make appropriate decisions what ensures the financial independence of the enterprise from external sources of financing and guarantees financial stability and affects the level of competitiveness of the enterprise; to create and manage opportunities; willingness of the management team to make changes, to take risks; formation of the actual potential of enterprises. Effective action of economic entities in Ukraine requires management of financial resources, at the expense of own capital of the enterprise which will involve bases for stable development of the enterprise and its constant growth in the market. The basic notion which lay at the heart of the system is “the cost of capital”. Therefore, every decision related to the management of equity must be made in terms of its impact on the value of the enterprise in general. Experience by domestic enterprises shows that investors prefer those companies where effective equity management operates, which will protect the interests and show the effect of the use of their investments. Capital is necessary attribute of the enterprise's activities from the moment of creation of the company to its liquidation or reorganization. In this way managerial efficiency is very important for the enterprise.